Editorial. Issue 1 (1st June 2022) - Travaglino, Giovanni A.
Abstract : The current organization of academic institutions creates a tension between knowledge and social change. Many scholars put inequality at the center of their research agenda. But they may also be subject to logics of exploitation linked to the commodification and marketization of knowledge and the precarization of the workplace. Such a struggle may appear especially salient now in British universities, where a long series of strike actions are taking place over pay equality and pay levels, casualization, and workload.